Myoferlin alleviates pressure overload-induced cardiac hypertrophy and dysfunction by inhibiting NLRP3-mediated pyroptosis - Zhou,Yang; Liu,Yanxu; Luo,Hao; Wen,Cong; Cui,Yangyang; Du,Linqing; Kwaku,Ofe Eugene; Li,Lan; Xiong,Lijuan; Zheng,Jiankang; Ding,Xuefeng; Shen,Xiufeng; et al. (PeerJ, 2024)
Myoferlin (MYOF) is a muscle-derived secretory protein. Recent studies have found that MYOF protects against cell damage. However, the role of MYOF in cardiac hypertrophy remains unclear. Increasing evidence suggests that NLRP3 (NOD-like receptor protein 3) and the pyroptosis cascade play critical roles in the development of cardiac hypertrophy and inflammation. To investigate the role of MYOF in cardiac hypertrophy, we conducted a transverse aortic constriction (TAC) experiment in a mouse model. We found that MYOF can improve cardiac hypertrophy and cardiac function. Furthermore, our study confirmed a connection between cardiac hypertrophy and myocardial pyroptosis. Cardiac hypertrophy significantly increased the proportion of apoptotic cells and upregulated apoptosis-associated speck-like protein containing a CARD (ASC), caspase-1, and gasdermin D (GSDMD). This suggests that pharmacological or genetic inhibition of NLRP3 can effectively reduce cardiac hypertrophy. An abnormal increase in NLRP3 can reverse the cardioprotective effects of MYOF. Our findings indicate that MYOF is a potential therapeutic agent for cardiac hypertrophy.
Keywords: Cardiac hypertrophy; Myoferlin; NOD-like receptor protein 3(NLRP3); Caspase 1 (CASP1)